Entre mito e racionalidade docente: uma compreensão da relação pedagógica na figura de Eco e Narciso - Luiz, Ercília Maria de Moura Garcia (2008)
The work Consists of a hermeneutic reflexion on the teaching image before the rationalist world, having as a starting point two critical studies by Theodor W. Adorno: Taboes that hover over the teaching profession and Philosophy and teachers. In such context, these mainly analyzed rectified phenomena, as well as contemplating an explanation of the subject-object scheme, are focused through the figurehead of professorial language and language as experience and revelation of world. In this sense, we seek to investigate how the figure of language of Eco and Narcissus can help in the pedagogical professorial understanding. Thus, we consider the systemic reason sprung from illuminism returns to the myth, by validating the tecnical-scientific world and the person s reification; action instrumental despite the professorial communicative action. This other rationality, which we seek here to approach, activates the premisse that efective comunication within the pedagogical relationship must transcend the metamorphosis of pathological languages such as those of Narcissus and Eco, as well as the overcoming of the same in hermeneutic texture. This way, through comprehension in the pedagogical relationship, involves more than mythical metalanguage, but an opening to comunicative action. If everything is language, even taboos, when crystalized in this world, dissolve along with the apory of the relationship subject-object. Finaly, in this way, we situate Jürgen Habermas' comunicative reason as another horizon to the pedagogical relation in contemporary times.